The shortwave infrared bands response to stomatal conductance in Conference" Pear Trees (Pyrus communis L.)" - Struthers, R.; Ivanova, A.; Tits, L.; Swennen, Rony L.; Coppin, P. (MDPI, 2015)
In situ measurements consisting of stomatal conductance, air temperature, vapor pressure deficit and the spectral reflectance in the shortwave infrared (SWIR) regions of thirty “Conference” pear trees (Pyrus communis L.) were repeatedly measured for eighty-six days. The SWIR was segmented into eight regions between 1550 and 2365 nm, where distances ranged from 40–200 nm. Each of the regions was used to describe the change in canopy water status over a period of approximately three months. Stomatal conductance of the water stress treatment was first determined to be significantly different from the control group nine days after stress initiation. The most suitable SWIR region for this study had wavelengths between 1550 and 1750 nm, where the first significant difference was also measured nine days after stress was initiated. After the period of water stress ended, forty-seven days after stress was initiated, all of the trees received full irrigation, where the SWIR region between 1550 and 1750 nm determined that stomatal conductance of the stress treatment lagged behind the control group for thirty days. Using a temporal sequence of SWIR measurements, we were able to successfully measure the beginning and the recovery of water stress in pear trees.